ANALISIS KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK BERDASARKAN FRISCO DALAM MATERI FUNGSI DI KELAS VIII - Mita Elia Sima; Yulis Jamiah; Edy Yusmin (Universitas Tanjungpura, 2022)
AbstrackThis study intends to decide and depict understudies' decisive reasoning abilities as faras orientation in light of FRISCO in learning mathematics, especially the functionmaterial. The technique utilized in this study is descriptive.The examination subjects inthis review were eighth-grade understudies of SMP Kemala Bhayangkari who werechosen because of purposive sampling.Gathering information for this concentratedthrough tests and interviews.From the aftereffects of the review, it was observed thatmale understudies and female understudies had the option to write down what they knewand asked, but female students wrote down information that wasn’t needed.Malestudents give reasons for each step quickly, concisely, logically, and relevant, but errorsstill often occur so that the conclusions made are inaccurate, while female students givereasons for each step in a detailed and careful systematic manner so they can describeconclusions correctly. Male understudies and female understudies can utilize all thedata on the inquiries. Male understudies tend not to know about other numerical ideasin the issue.Male understudies and female understudies can explain the meaning of thesymbols they used. Male students re-examine their answers and believe in the answers,but female students don't re-check their answers and tend not to believe.Keywords: Critical Thinking, FRISCO, Function Material, Gender